A Beginner’s Guide to Water Management — Lake Morphometry - Florida LAKEWATCH (EDIS, 2003)
This document, CIR 104, is the fourth of a series of information circulars dedicated to familiarizing citizens with the language and techniques used by those involved in water management within the state of Florida. First printed in April 2001. This is the second edition, published in September 2001.